PENINGKATAN KEMAMPUAN MENYIMAK ANAK USIA DINI DENGAN MEDIA BONEKA TONGKAT - Ayunda Sayyidatul Ifadah (JCE (Journal of Childhood Education), 2020)
This study aims to determine the effect of the use of puppet media on the ability to listen to children in group A TK N Pembina District Gresik. This study used the Quasi Experiment research method with the Nonequivalent Control Group Design type. The population of this study were all TK N Pembina District children in Gresik, with samples class A1 as the experimental class and A2 as the control class. The data collection technique used is observation. The results showed that the effect of the use of puppet media on the ability to listen to children in group A TK N Pembina District of Gresik, this was evidenced from the results of t test calculations obtained p value 0.00 less than 0.05